FROM CLOSE TO DISTANT READING OF 100 ROMANIAN NOVELS FROM 1850 TO 1920 - Luiza MARINESCU (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
From Close to Distant Reading of 100 Romanian Novels from 1850 to 1920. In Romania, among the academic personalities, Solomon Marcus (b. the 1st of March 1925, Bacău – d. the 17th of March 2016, Bucharest) was perhaps the only one who happily combined linguistics and mathematics, being known in the Romanian philological environment especially for Lingvistica matematică [Mathematical Linguistic], Modele matematice în lingvistică [Mathematical Models in Linguistics], 1963, 1966, and Poetica matematică [Mathematical Poetics], in 1970, and in the international scientific field for numerous translation and also for numerous papers published in prestigious publishing houses in Paris, New York and Bologna.